A simple potentiometric biosensor based on carboxylesterase for the analysis of aspartame - Noor Izaanin Ramli,; Lee, Yook Heng; Tan, Ling Ling (Penerbit Universiti Kebangsaan Malaysia, 2022)
A potentiometric aspartame biosensor was fabricated by simply depositing the carboxylesterase (CES)-bonded poly(n-butyl acrylate-n-acryloxysuccimide) [CES-poly(nBA-NAS)] microspheres on a Ag/AgCl screen-printed pH selective electrode. The pH transducer was made from non-plasticized polyacrylate membrane containing a hydrogen ionophore and lipophilic salt. The immobilized CES enzyme catalyzed the enzymatic hydrolysis of aspartame to L-aspartic acid (L-Asp), L-phenylalanine and methanol. Potentiometric determination of aspartame concentration was performed by quantifying the hydrogen ion concentration produced from L-Asp. The potentiometric determination of aspartame exhibited good selectivity with near Nernstian response. The sensitivity of the biosensor was closed to the Nernstian value, i.e., 50-52 mV decade-1 with a dynamic linear response range from 10-5 to 10-2 M and detection limit approaching 10-6 M. The aspartame biosensor demonstrated good repeatability and reproducibility with relative standard deviation (RSD) of 1.9% and 1.6%, respectively (n=3). The potentiometric aspartame biosensor was demonstrated to be reliable for determining aspartame content in sweetener samples and was comparable to the conventional high-performance liquid chromatography (HPLC) method for aspartame analysis.